Plasmid pT181 replication is regulated by two countertranscripts. - Kumar, C C (1985)
A transcription map of the replication control region of the Staphylococcus aureus plasmid pT181 has been constructed. Two major leftward transcripts, RNA III and RNA IV, start at positions 339 and 413, respectively. These two RNAs can serve as mRNAs for a plasmid-specific replication protein RepC. Two short rightward transcripts, RNA I and RNA II, approximately 85 and 150 nucleotides long, respectively, start at position 246. These rightward transcripts (referred to as countertranscripts) do not appear to be translated but act directly as negative regulators of plasmid replication, probably by interfering with translation of the RepC mRNAs. There is no significant base sequence homology among the countertranscripts of pT181, ColE1, and R1/NR1/R6-5, suggesting that the structural parallelism has risen by convergent molecular evolution.